2018
DOI: 10.1016/j.joen.2018.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Tricalcium Silicate Capping Materials Modulate Pulp Healing and Inflammatory Activity In Vitro

Abstract: These results confirm that pulp-capping materials affect the early steps of pulp inflammation and healing. They show that Biodentine had the highest pulp healing and anti-inflammatory potential when compared with the resin-containing materials. This highlights the interest of the material choice for direct pulp-capping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
59
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 34 publications
1
59
0
3
Order By: Relevance
“…Our results are consistent with other studies that have shown the migration capacity of the root repair materials. For example, iRoot FS (Innovative Bioceramix, Vancouver, BC, Canada) showed cell migration rates higher than ProRootMTA (Dentsply, Tulsa, OK, USA) [28], or Biodentine (Septodont, St Maur des Fosses, France) has been evidenced by anti-inflammatory properties and favored fibroblast migration to the injury site [31]. Nevertheless, the detailed mechanism of how premixed and putty calcium silicate materials favors cell migration is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Our results are consistent with other studies that have shown the migration capacity of the root repair materials. For example, iRoot FS (Innovative Bioceramix, Vancouver, BC, Canada) showed cell migration rates higher than ProRootMTA (Dentsply, Tulsa, OK, USA) [28], or Biodentine (Septodont, St Maur des Fosses, France) has been evidenced by anti-inflammatory properties and favored fibroblast migration to the injury site [31]. Nevertheless, the detailed mechanism of how premixed and putty calcium silicate materials favors cell migration is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the resin in pulp capping materials such as ACTIVA BioACTIVE BASE/LINER would presumably shift the regeneration-inflammation balance towards the latter. As in the other light-cured tricalcium silicate, incomplete resin photopolymerization may lead to free monomers' release, and consequently to pulpal toxicity [137]. However, to accurately assess ACTIVA BioACTIVE's reparative potential or influence on the vital pulp in pulp capping procedures, further in vitro and in vivo studies are necessary.…”
Section: Activa Bioactivementioning
confidence: 99%
“…It is proved that calcium-silicate cements used for direct pulp capping affect the the form of direct pulp capping [1][2][3]. It is proved that calcium-silicate cements used for direct pulp capping affect the initial inflammatory stages and induce the healing process [4]. The currently used MTA is considered the golden standard in the biological treatment of the pulp [5].…”
Section: Introductionmentioning
confidence: 99%
“…Under physiological conditions, macrophages are present in the pulp in a dormant state. Only during the development of the inflammatory process, do they show mobility and move to the site of inflammation [3][4][5]9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation